2022
DOI: 10.3390/s22145184
|View full text |Cite
|
Sign up to set email alerts
|

Vision-Based Detection of Bolt Loosening Using YOLOv5

Abstract: Bolted connections have been widely applied in engineering structures, loosening will happen when bolted connections are subjected to continuous cyclic load, and a significant rotation between the nut and the bolt can be observed. Combining deep learning with machine vision, a bolt loosening detection method based on the fifth version of You Only Look Once (YOLOv5) is proposed, and the rotation of the nut is identified to detect the bolt loosening. Two different circular markers are added to the bolt and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 44 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…This idea omits the complex candidate box selection and calculation steps in the two-stage algorithm. Therefore, the running speed of the algorithm is far faster than that of the two-stage detection algorithm [ 27 , 28 , 29 ]. The representative algorithms are the YOLO algorithm and the SSD algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…This idea omits the complex candidate box selection and calculation steps in the two-stage algorithm. Therefore, the running speed of the algorithm is far faster than that of the two-stage detection algorithm [ 27 , 28 , 29 ]. The representative algorithms are the YOLO algorithm and the SSD algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang (2020) et al proposed a bolt loosening detection method based on Fast-RCNN algorithm, using the bolt thread heights under different loosening states. Sun et al (2022) identified the marks on the nut and the screw to determine the loosening of bolt based on YOLOv5.…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al 35 combine target detection algorithm and target tracking algorithm to detect and track bolt looseness. Sun et al 36 use YOLOv5 algorithm to detect bolts and marks on bolts, and calculate the bolt loosening angle according to the central coordinates of two types of boundary frames. Huynh et al 37 detected and cut the bolt area through convolutional neural network, and then identified the bolt loosening angle based on Hough transform.…”
Section: Introductionmentioning
confidence: 99%